Some aspects of constitutional fixation of the principles of electoral law in the Republic of Kazakhstan and foreign countries - Yerzhanova, F.A. (Bulletin of the Karaganda University “Law Series”, 2019)
In the scientific article the theoretical and legal aspects and the constitutional and legal basis of the principles of electoral law of the Republic of Kazakhstan and foreign countries based on the analysis of the current constitutional and legal legislation of the Republic of Kazakhstan and foreign countries, legal literature in the field of electoral law and process, international documents are discussed. Much attention is paid to the study of the provisions of the Constitution of the Republic of Kazakhstan and the constitutions of foreign countries, the Constitutional Law of the Republic of Kazakhstan «On Elections in the Republic of Kazakhstan», enshrining the fundamental principles of electoral law. The analysis of international and legal norms on the principles of electoral law is given, the opinions of legal scholars are examined, and topical issues of constitutional reflection of the principles of electoral law are highlighted. The author considers the regulation of some election principles, touched upon some of the problems of restriction of suffrage. The need for further improvement of constitutional and electoral legislation was established, proposals for the introduction of amendments and additions to the constitutional and legal legislation of the Republic of Kazakhstan in the sphere of regulating the basic principles of electoral law and the process were formulated. In the article the foreign experience of constitutional and regulation of the basic principles of electoral law is discussed. The main directions for improving the constitutional and legal regulation of the principles of electoral law are: enshrining universal principles of electoral law in constitutional legislation on elections; systematization of principles of electoral law.